AUTHORSHIP IN AN ESSAY ON INDIAN COMMUNITY JURUNA: PERSPECTIVES AND EVIDENCE - Moscardini, Ligia Egidia [UNESP] (Fundacao Univ Tocantins, 2017)
This article has, as its objective, discuss questions about copyright and authorship in an essay from a indigenous student. For that, first, we investigate the notion of author on classical vision of Foucault (2001) of Foucault (2001) and then observe how as such notions are present in school texts according to Orlandi (1987), Pfeiffer (1995), Possenti (2002) and Possenti (2016), as well as the requirements and conditions that the school offers to the student to become a competent writer. Then, we look for highlight, by Indicting Paradigm, on what makes a school text have indications of authorship to then investigate traces of authorship in the latest version of a text, in Portuguese as a second language, written by a student from juruna school in textual production workshop held in July 2013.
Keywords: School Essay; Portuguese as a second language; Evidence of authorship